2020
DOI: 10.3389/fmolb.2019.00156
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Extracellular Complexity of Neuromuscular Junction Organizers

Abstract: Synapse formation is a very elaborate process dependent upon accurate coordination of pre and post-synaptic specialization, requiring multiple steps and a variety of receptors and signaling molecules. Due to its relative structural simplicity and the ease in manipulation and observation, the neuromuscular synapse or neuromuscular junction (NMJ)-the connection between motor neurons and skeletal muscle-represents the archetype junction system for studying synapse formation and conservation. This junction is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 209 publications
(337 reference statements)
0
25
0
Order By: Relevance
“…While many additional signalling pathways have been identified that play a role in synapse specialization, including neuregulin/ErbB, Wnt/ÎČ-catenin, and Hippo/Yes-associated protein signalling cascades [40] , the remainder of this section will emphasize molecules that have been examined in the DMD context and how they develop, maintain, and remodel synaptic structure and function. Readers interested in much more comprehensive surveys of NMJ maturation are enthusiastically referred to these recent, expert reviews [ 20 , 22 , 23 , 37 , 40 , 41 ].…”
Section: Development Maintenance and Plasticity Of The Nmjmentioning
confidence: 99%
“…While many additional signalling pathways have been identified that play a role in synapse specialization, including neuregulin/ErbB, Wnt/ÎČ-catenin, and Hippo/Yes-associated protein signalling cascades [40] , the remainder of this section will emphasize molecules that have been examined in the DMD context and how they develop, maintain, and remodel synaptic structure and function. Readers interested in much more comprehensive surveys of NMJ maturation are enthusiastically referred to these recent, expert reviews [ 20 , 22 , 23 , 37 , 40 , 41 ].…”
Section: Development Maintenance and Plasticity Of The Nmjmentioning
confidence: 99%
“…It involves the neuron-secreted proteoglycan agrin with its receptor, the lipoprotein receptor-related protein 4 (LRP4), the muscle-specific kinase (MuSK) and the regulatory soluble synapse-specific protease Neurotrypsin. Since MuSK is not able to directly bind Agrin, LRP4 mediates the process by forming a stable receptor/co-receptor assembly (for a complete review see [ 1 ]). The complex interplay between motor axons, terminal Schwann cells and the muscle fibers of the peripheral nervous system (PNS), is reminiscent of the tripartite synapse in the central nervous system (CNS) where pre- and post-synaptic neurons and astrocytes interact ( Figure 1 ).…”
Section: Nmj Structural Architecture and Peculiaritiesmentioning
confidence: 99%
“…Lrp4 (Pink frame, Figure 1) which plays a pivotal role in mediating agrin (via green-limit, MuSK lg1/2, Figure 1)-and Wnt (via red-limit, MuSK CRD, Figure 1)-signalings for AChR clustering at the postsynaptic membrane and also serves the retrograde signaling from muscle to nerve (Barik et al, 2014a;Guarino et al, 2020). The molecular structure of Lrp4 consists of a large extracellular domain that contains eight low-density lipoprotein receptor domains class A (LDLa), EGF-like domains and four ÎČ-propeller domains; its N-terminal region (including the last few LDLa repeats and the first ÎČ-propeller domain) interacts with agrin (Zhang et al, 2011;Zong et al, 2012); in its third ÎČ-propeller domain, the edge part mediates the MuSK signaling and the central part mediates the Wnt signaling (Ohkawara et al, 2014).…”
Section: Anti-lrp4 Antibodiesmentioning
confidence: 99%
“…Wnt 11 (Wu et al, 2010;Zhang et al, 2012a), Wnt 9a (Zhang et al, 2012a), and Wnt4 (Strochlic et al, 2012;Zhang et al, 2012a) are derived from muscles. The binding of the Ig4 domain (CRD) of MuSK (red-limit in pink MuSK, Figure 1) with Wnts contributes to AChR clustering through the non-canonical pathway mediated by the Dishevelled protein (Dvl; Pink frame, Figure 1), leading to the formation of AChR microclusters at the early non-innervated stage, termed as the AChR prepatterning (Kummer et al, 2006) which forms the clusters at the central part of the muscle and guides the incoming axon (Gray frame, Figure 1; Luo et al, 2002;Jing et al, 2009;Stiegler et al, 2009;Wu et al, 2010;Gordon et al, 2012;Koles and Budnik, 2012;Barik et al, 2014b;Burden et al, 2018;Guarino et al, 2020). The motoneuron-derived Wnt7a and Wnt7b serve nerve terminal development (Shen et al, 2018).…”
Section: Wnt-mediating Signal Via Musk Contributes To Achr Cluster Prmentioning
confidence: 99%